Predição genômica para o peso ao sobreano via norma de reação em bovinos de corte - Oliveira, Daniele Portela de [UNESP] (2016)
The growing of beef cattle breeding programs and the demand for animals for slaughter at young ages related with variety of climates conduced researches in genotype environmental interaction (GxE). The way to choose the top animals in young ages is include the genomic information on genetic evaluations. The aim of this study was to examine reaction norm models with genomic information by the relationship matrix with pedigree plus genotypes and looking for related genes with the yearling weight. The yearling weights from Nellore animals with about 520 days of age were used. A total of 5.091 animals were genotyped with a panel of 777,962 SNPs (IlluminaBovineHDBeadchip). The variance components were estimated through restricted maximum likelihood with A -1 and H -1 matrix. To compare the predictive ability of the methods, the following procedures were used: correlation between the genomic values (GEBV) and the predicted phenotypes and the correlation value divided by the square root of the heritability for each GA. Genotyped animals born between 2009 and 2011 were the test population. The results of the genome association analysis (GWAS) have been presented based on the proportion of variance explained by windows of 200 adjacent SNPs; and the top of two windows were studied. In chapter 2 the environmental gradients (EG) were composed by farm and birth age effects. Estimates of genetic parameters suggest the GxE; and the model with H matrix was 19% higher compared with the model with only pedigree on relationship matrix. Chromosomes 14 and 27 were the most important on the EG. In chapter 3 the EG were based on iterative process proposed in prior researches. The results of variance components for intercept and slope were almost the same for both models. The CSDM3 was the most important gene identified on reaction norm slope, because it was found in beef cattle before.